Multiple blood-brain barrier transport mechanisms limit bumetanide accumulation, and therapeutic potential, in the mammalian brain. (1st May 2017) - Römermann, Kerstin; Fedrowitz, Maren; Hampel, Philip; Kaczmarek, Edith; Töllner, Kathrin; Erker, Thomas; Sweet, Douglas H.; Löscher, Wolfgang
Abstract: There is accumulating evidence that bumetanide, which has been used over decades as a potent loop diuretic, also exerts effects on brain disorders, including autism, neonatal seizures, and epilepsy, which are not related to its effects on the kidney but rather mediated by inhibition of the neuronal Na-K-Cl cotransporter isoform NKCC1. However, following systemic administration, brain levels of bumetanide are typically below those needed to inhibit NKCC1, which critically limits its clinical use for treating brain disorders. Recently, active efflux transport at the blood-brain barrier (BBB) has been suggested as a process involved in the low brain:plasma ratio of bumetanide, but it is presently not clear which transporters are involved. Understanding the processes explaining the poor brain penetration of bumetanide is needed for developing strategies to improve the brain delivery of this drug. In the present study, we administered probenecid and more selective inhibitors of active transport carriers at the BBB directly into the brain of mice to minimize the contribution of peripheral effects on the brain penetration of bumetanide. Furthermore, in vitro experiments with mouse organic anion transporter 3 (Oat3)-overexpressing Chinese hamster ovary cells were performed to study the interaction of bumetanide, bumetanide derivatives, and several known inhibitors of Oats on Oat3-mediated transport. The in vivo experiments demonstrated that the uptake and efflux of bumetanide at the BBB is much more complex than previously thought. It seems that both restricted passive diffusion and active efflux transport, mediated by Oat3 but also organic anion-transporting polypeptide (Oatp) Oatp1a4 and multidrug resistance protein 4 explain the extremely low brain concentrations that are achieved after systemic administration of bumetanide, limiting the use of this drug for targeting abnormal expression of neuronal NKCC1 in brain diseases. Highlights: Bumetanide is the only drug that selectively inhibits the Na-K-Cl contransporter NKCC. Increased expression of neuronal NKCC1 seems to involved in several brain diseases. Using bumetanide for inhibiting neuronal NKCC1 is hampered by its low brain:plasma ratio. We suppressed blood-brain barrier efflux transporters by intracerebral injection of inhibitors. Different members of Oat and Oatp transport families are involved in bumetanide efflux.